Au(111) Surface Contamination in Ambient Conditions: Unravelling the Dynamics of the Work Function in Air. Issue 10 (23rd March 2021) - Turetta, Nicholas; Sedona, Francesco; Liscio, Andrea; Sambi, Mauro; Samorì, Paolo
Abstract: Gold is an inert noble metal displaying superior chemical stability that renders it a suitable component for the manufacturing of electrodes for various types of devices. Despite being widely employed, the variation of gold surface properties occurring upon the material's exposure to ambient conditions have been often disregarded. While it is well‐known that the contamination of a metallic surface can have a dramatic impact on its properties, the process of contamination itself is poorly understood. Changes of the work function by fractions of an electron‐volt are commonly observed in gold surfaces that are processed at ambient laboratory conditions, but an exhaustive comprehension and control of this phenomenon are still lacking. Here, a multiscale characterization of Au(111) surfaces aiming to unravel the surface dynamics underlying the air contamination is presented. The visualization of the adventitious carbon contamination on Au(111) surface by atomic force microscopy is key to rationalize the mechanisms of surface reorganization ruling the change of Au work function between 5.25 and 4.75 eV by solely changing the storage conditions. Such a huge variation must be taken into account when optimizing the Au surface for both controlling its fundamental surface and interfacial physical processes, as well as its functional applications. Abstract : An in‐depth investigation on the most relevant surface and interface properties of Au(111) when subjected to ambient contamination upon exposure to air is reported. Work function changes up to 500 meV are demonstrated and correlated to the time evolution of the morphology. Various complementary surface techniques are employed to rationalize the surface dynamics underlying the change of Au work function.